PENGEMBAGAN MODEL SITFD ( STUDET INTERACTIVE TEAM FOCUS DISSUSION) DALAM PEMBELAJARA IPS DI SEKOLAH DASAR - Afifah, Nervilia Nur; Nurasiah, Iis; Uswatun, Din Azwar (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
Education is a conscious effort made by educators to create a learning atmosphere and learning process so that students are more active in developing their potential, intelligence, personality, noble character, and skills needed when in society. Developing the potential of students who are creative, knowledgeable, independent, and become democratic citizens can be achieved through subjects at school, one of which is through Social Sciences (Social Science) subjects. IPS learning is one of the main subjects at the elementary school level. IPS education has a fairly broad range of material, because IPS education covers social symptoms and life problems in society. Social studies education helps students in solving the problems they face so that it will make them understand and understand the social environment of the community more. Given that, students' abilities differ, especially in terms of remembering. So that we need a learning model with a method that fits the criteria of elementary school students who are still synonymous with the word play, interact and have fun. Keywords: Development, primary school IPS(social studies education), Learning model.